Independent and joint associations of sleep quality and physical activity with glycaemic control in patients with type 2 diabetes mellitus - Zhou, Lei; Li, Yize; Zhang, Shuo; Zhang, Haimeng; Ji, Xiaomei; Yu, Yuanyuan; Xie, Hong (Frontiers in Nutrition, 2025)
BackgroundAlthough determinants of glycaemic control in type 2 diabetes mellitus (T2DM) have been extensively investigated, the joint influence of sleep quality and physical activity (PA) remains insufficiently studied. We aimed to examine the independent and combined associations of sleep quality and PA with glycaemic control in patients with T2DM.MethodsWe conducted a cross-sectional study of 329 patients with T2DM. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). PA was self-reported through questionnaires and expressed as metabolic equivalents (METs). Associations between sleep quality, PA, and glycaemic control were assessed using multivariable logistic regression.ResultsAfter adjusting for confounding factors, we observed that declining habitual sleep efficiency was associated with an increased risk of suboptimal glycaemic control (OR 1.64, 95% CI 1.14–2.43). Participants with poorer sleep quality had a higher risk of suboptimal glycaemic control compared with those with better sleep quality (OR 2.09, 95% CI 1.09–4.09). High PA was associated with a significantly lower risk of poor glycaemic control compared with low PA (OR 0.20, 95% CI 0.05–0.68). In combined analyses, the greatest reduction in the risk of poor glycaemic control was observed in participants with good sleep quality and moderate PA, compared to those with poor sleep quality and low PA (OR 0.38, 95% CI 0.14–0.98).ConclusionIn patients with T2DM, achieving optimal glycaemic control requires not only maintaining PA but also improving sleep quality.